Mechanisms of Control of Mycobacterium tuberculosis by NK Cells: Role of Glutathione - Allen, Michael; Bailey, Cedric; Cahatol, Ian; Dodge, Levi; Yim, Jay; Kassissa, Christine; Luong, Jennifer; Kasko, Sarah; Pandya, Shalin; Venketaraman, Vishwanath (Frontiers in Immunology, 2015)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (M. tb), continues to be one of the most prevalent infectious diseases in the world. There is an upward trend in occurrence due to emerging multidrug resistant strains and an increasingly larger proportion of immunocompromised patient populations as a result of the acquired immunodeficiency syndrome (AIDS) pandemic. The complex and often deadly combination of multidrug resistant M. tb (MDR-M. tb) along with human immunodeficiency virus (HIV) puts a significant number of people at high risk for pulmonary and extra-pulmonary TB without sufficient therapeutic options available. Natural Killer (NK) cells and macrophages are major components of the body’s innate immune system, contributing significantly to the body’s ability to synergistically inhibit the growth of M. tb in immune compromised individuals lacking a sufficient T cell response. Direct mechanisms of control are largely through the secretory products perforin, granulysin and granzymes, as well as multiple membrane-bound death receptors that facilitate target directed lysis. NK cells also have a role in indirectly stimulating an immune response through activation of macrophages and monocytes with multiple signaling pathways including both reactive oxygen species (ROS) and reactive nitrogen species (RNS). Glutathione (GSH) has been shown to play a part in inhibiting growth of intracellular M. tb through bacteriostatic mechanisms. Enhancing cellular GSH through several cytokines and N-acetyl cysteine (NAC) has been shown to increase these effects, at least in part, through their action on NK cells. Taken overall, there is substantial evidence for a mechanistic correlation between NK cell activity and functionality in combating M. tb in HIV infection mediated through adequate GSH production and use.